Perencanaan Kebutuhan Air Pada Areal Irigasi Bendung Walahar Karawang, Jawa Barat - Rika Sri Amalia; Budi Santosa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
Planning for water needs for irrigation areas is carried out to determine the water needs for plants to grow and develop. The source of water obtained for meeting water needs comes from the Walahar Dam. The results of water demand planning can also be used to simulate cropping patterns. Cropping patterns are very helpful for farmers in determining effective and efficient planting times. Calculation of plant water needs is processed from climatological data and rainfall data, the results of which are demand discharge. Based on the results of the calculation of water requirements for plants, the average discharge requirement is 0.65 m3/second – 9.59 m3/second, while the available water or available discharge in Walahar Weir is 183.90 m3/second. So it can be concluded that the available water in Walahar Weir can meet the water needs of plants. Keywords: Discharge, Climatological Data, Rainfall Data, Plant Water Demand Planning